Analysis of Code Mixing in The Speech of Coastal Communities - Nurohmah, Siti; Taiman; Supriyadin (IJESS International Journal of Education and Social Science, 2024)
This study aims to explore the phenomenon of code mixing in the speech of coastal communities of Karang Tawulan Beach, Tasikmalaya Regency. This study describes how local communities utilize code mixing between Sundanese, Indonesian, and foreign languages ??to form and maintain their linguistic identity. In addition, this study identifies the complexity of the influence of globalization that arises from interactions with tourists and immigrants from various backgrounds. The method used is descriptive qualitative with a sociolinguistic approach, emphasizing in-depth analysis of oral and written data. The results of the study indicate that code mixing is in the form of word insertion, phrases, and word repetition. Influencing factors include speech partners, communication situations, and communication goals. This study provides important insights into communication strategies in multilingual societies and suggests significant contributions to the development of language and education policies in the era of globalization, with the aim of supporting the preservation of regional languages ??in Indonesia.